2022
DOI: 10.20527/jipf.v6i1.4079
|View full text |Cite
|
Sign up to set email alerts
|

Kepraktisan Buku Ajar Listrik Magnet Seri 2 Bermuatan Ayat-Ayat Al-Qur’an Menggunakan Model Pembelajaran Connecting-Organizing-Reflecting-Expanding

Abstract: Tujuan dari penelitian ini adalah mendeskripsikan kepraktisan buku ajar listrik magnet Seri 2 bermuatan ayat-ayat Al-Qur’an menggunakan model pembelajaran CORE (Connecting-Organizing-Reflecting-Expanding). Jenis penelitian ini adalah penelitian dan pengembangan dengan menggunakan model 4D. Penelitian ini menggunakan mahasiswa calon guru fisika berjumlah 14 orang yang sedang mempelajari topik listrik pada mata kuliah listrik magnet di tahun akademik 2020/2021 sebagai subjek ujicoba. Data dikumpulkan melalui ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
2
0
0
Order By: Relevance
“…Additionally, students have responded positively to its usefulness, convenience, and overall satisfaction with the model. These results align with the notion that teaching materials are considered practical if they are user-friendly and beneficial to users [54].…”
Section: Discussionsupporting
confidence: 83%
“…Additionally, students have responded positively to its usefulness, convenience, and overall satisfaction with the model. These results align with the notion that teaching materials are considered practical if they are user-friendly and beneficial to users [54].…”
Section: Discussionsupporting
confidence: 83%
“…Therefore, based on the assessment of expert validators of Islamic religious education, it can be concluded that the holy verses of the Qur'an, hadith and tafsir contained in eworksheet are relevant to the material excretion system. This is in accordance with the research of Fitriah & Rahmawati (2022) that teaching materials will have more significant benefits for students if combined with verses of the Qur'an. The inclusion of this religious content aims to unite religious science and modern sciences, Suciati et al (2022) explained that Islam and science are one unit.…”
Section: Components Before Revision After Revisionsupporting
confidence: 90%